Pengaruh Dosis Pupuk Kandang Ayam Terhadap Pertumbuhan dan Hasil Tanaman Kentang (Solanum tuberosum L.) Varietas Granola - Yudi Yusdian; Karya Karya; Riksa Vaisal (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2018)
The aim of this research is to get the dosage of chicken manure which can give the best effect on the growth and yield of potato (Solanum tuberosum L.) Granola Variety. The experiment was conducted in Marga Mekar Village Pangalengan District Bandung Regency West Java Province. With an altitude of ± 1,200 meters above sea level, Andisol soil type with pH 5.4. with rainfall of 1980,42 mm/year including type C2 rainfall according to Oldeman (1975). The experimental time from May until August 2017. The research method used was Randomized Block Design (RBD) consisting of six treatments and four replications. The treatment of chicken manure is as follows A (0 ton / Ha), B (6 ton / Ha), C (8 ton / Ha), D (10 ton / Ha), E (12 ton / Ha) and F (14 ton / Ha). The results showed that the application of chicken manure with Dosage 6 ton / ha gave better effect to plant height, while the dosage of 12 ton / ha gave the best effect to weight of tuber per potato plant (Solanum tuberosum L.) Granola Variety.